2017
DOI: 10.1016/j.msec.2017.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of thermal sensitive folic acid based supramolecular hybrid gels for injectable drug release gels

Abstract: Thermal sensitive supramolecular hybrid gels for injectable drug release were prepared by adding different amounts of agar into folic acid (FA) gelator. The gelation temperature was modulated in order to form injectable gel with body temperature (37°C). Such kind of folic acid-agar (FAG) hybrid gel makes it possible to use supramolecular gel as injectable drug loaded gels for drug release. FT-IR and UV-vis spectra indicate that agar macromolecules involve in the self-assembly process through intermolecular H-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Supramolecular hydrogels have attracted considerable attention due to their potential applications as promising biomaterials for many biotechnological and biomedical applications, such as drug delivery [1,2], cell culture [3], tissue engineering [4], wound healing [5,6], and many others. Upon receiving an external trigger, short peptides capped with aromatic groups on the N-terminus can often self-assemble into three-dimensional (3D) networks, forming fibers that can trap water molecules, providing biocompatible and biodegradable supramolecular hydrogels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular hydrogels have attracted considerable attention due to their potential applications as promising biomaterials for many biotechnological and biomedical applications, such as drug delivery [1,2], cell culture [3], tissue engineering [4], wound healing [5,6], and many others. Upon receiving an external trigger, short peptides capped with aromatic groups on the N-terminus can often self-assemble into three-dimensional (3D) networks, forming fibers that can trap water molecules, providing biocompatible and biodegradable supramolecular hydrogels [7].…”
Section: Introductionmentioning
confidence: 99%
“…The abilities of supramolecular gels to include temperature-sensitive functionality, rheological tunability, and stability when used as a platform for drug release have garnered interest in their use for injectable drug delivery applications. A thermally-sensitive folic acid-agar supramolecular hybrid gel in a 1:1 DMSO-water mixture by Song et al demonstrated mechanical tunability and a drug release profile with a low initial burst and long release time with a model drug [101]. With a specific application in mind, Dai et al developed a supramolecular gel in aqueous media based on host-guest inclusion complexation between α-cyclodextrin and anti-tumor drug-loaded micelles that exhibited several notable properties, including facile preparation, high stability, an attractive drug release profile, low toxicity, and effective in vitro and in vivo anti-tumor activity [102].…”
Section: Supramolecular Gels For Biomedical Applicationsmentioning
confidence: 99%
“…Supramolecular hydrogels have attracted considerable attention due to their potential applications as promising biomaterials for many biotechnological and biomedical applications, such as: drug delivery, [1,2] cell culture, [3] tissue engineering, [4] wound healing [5,6] and many others. Upon receiving an external trigger, short peptides capped with aromatic groups on the Nterminus can often self-assemble into three-dimensional (3D) networks, forming fibres which can trap water molecules, providing biocompatible and biodegradable supramolecular hydrogels [7].…”
Section: Introductionmentioning
confidence: 99%